The Effect of Social Media, Worth of Mouth, Brand Image on Increasing Home Sales of the Tempe Industry - Choirunnisa Choirunnisa; Bayu Eko Broto; Nurintan Asyiah Siregar (PT Mattawang Mediatama Solution, 2022)
This study aims to determine the Effect of Social Media, Worth Of Mouth, Brand Image on Increasing Home Sales of the Tempe Industry. The method in this study is a quantitative method. Based on the results of the t test, it is known that the Worth Of Mouth and Brand Image variables have a partial and significant effect on increasing sales of Home Industry Tempe based on Sig < 0.05 and t count > t table (1.984), while the Social Media variable has no partial and significant effect on increase in sales of Home Industry Tempe based on Sig Value > 0.05 and t count < t table (1.984). It is concluded that Social Media, Wort of Mouth , Brand Image simultaneously affect the increase in Home Sales of the Tempe Industry in terms of Sig. < 0.05 and based on the calculated f value 542.310 > from f table 2.70. Based on the R-Square of 0.944, the value of the contribution of the impact of Social Media, Wort of Mouth, Brand Image simultaneously affects the increase in Home Sales of the Tempe Industry by 94.4% and the remaining 5.6% is influenced by other factors outside of this study